BOLUS TEMULAWAK IMPLEMENTATION ON BEEF CATTLE IN SELOGABUS VILLAGE, PARENGAN, TUBAN REGENCY - Siti Eliana Rochmi; Retno Sri Wahjuni; Miyayu Soneta Sofyan (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: The beef cattle farming in Tuban area is mostly on a small scale and traditionally maintained. In general, the nutritional adequacy of the animal feed provided is not optimal, while the potential for livestock in the area is quite large. There are still few breeders who provide concentrates on the grounds that the high costs incurred so that the weight growth of beef cattle is still not optimal. Bolus Temulawak is an animal feed substitute for concentrate with temulawak as an additive. Objective: This activity aims to strengthen the economy of beef cattle farmers through the introduction, dissemination, and transfer of temulawak bolus technology as an alternative feed with sufficient nutritional value for beef cattle so that daily weight gain can be maximized. Methods: This activity held towards community empowerment such as coaching related to feed and livestock health by FGD (Focus Group Discussion) followed by training on making Bolus Temulawak and application of Bolus Temulawak to beef cattle. Evaluation of this activity is pre and post test of community service participants, as well as body weight measurement of beef cattle before and after being given Bolus Temulawak. Results: The results of this community service are an increase in daily body weight of beef cattle, as well as an increase in the knowledge and skills of community service participants. Conclusion: Community service activities have a positive impact on the development of beef cattle farms in partner areas.